Development of plastic-degrading microbial consortia by induced selection in microcosms - Salinas, Jesús; Carpena, Víctor; Martínez-Gallardo, María R.; Segado, Martín; Estrella-González, María J.; Toribio, Ana J.; Jurado, Macarena M.; López-González, Juan A.; Suárez-Estrella, Francisca; López, María J. (Frontiers in Microbiology, 2023)
The increase in the production of highly recalcitrant plastic materials, and their accumulation in ecosystems, generates the need to investigate new sustainable strategies to reduce this type of pollution. Based on recent works, the use of microbial consortia could contribute to improving plastic biodegradation performance. This work deals with the selection and characterization of plastic-degrading microbial consortia using a sequential and induced enrichment technique from artificially contaminated microcosms. The microcosm consisted of a soil sample in which LLDPE (linear low-density polyethylene) was buried. Consortia were obtained from the initial sample by sequential enrichment in a culture medium with LLDPE-type plastic material (in film or powder format) as the sole carbon source. Enrichment cultures were incubated for 105 days with monthly transfer to fresh medium. The abundance and diversity of total bacteria and fungi were monitored. Like LLDPE, lignin is a very complex polymer, so its biodegradation is closely linked to that of some recalcitrant plastics. For this reason, counting of ligninolytic microorganisms from the different enrichments was also performed. Additionally, the consortium members were isolated, molecularly identified and enzymatically characterized. The results revealed a loss of microbial diversity at each culture transfer at the end of the induced selection process. The consortium selected from selective enrichment in cultures with LLDPE in powder form was more effective compared to the consortium selected in cultures with LLDPE in film form, resulting in a reduction of microplastic weight between 2.5% and 5.5%. Some members of the consortia showed a wide range of enzymatic activities related to the degradation of recalcitrant plastic polymers, with Pseudomonas aeruginosa REBP5 or Pseudomonas alloputida REBP7 strains standing out. The strains identified as Castellaniella denitrificans REBF6 and Debaryomyces hansenii RELF8 were also considered relevant members of the consortia although they showed more discrete enzymatic profiles. Other consortium members could collaborate in the prior degradation of additives accompanying the LLDPE polymer, facilitating the subsequent access of other real degraders of the plastic structure. Although preliminary, the microbial consortia selected in this work contribute to the current knowledge of the degradation of recalcitrant plastics of anthropogenic origin accumulated in natural environments.